Enhacement of Microgrid Technologies using Various Algorithms (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The electric power systems around the globe are gradually shifting from conventional fossil fuel-based generating units to green renewable energy sources. The motivation behind this change is the environmental and economic concerns. Furthermore, the existing power systems are being overloaded day by day due to the continuously increasing population, which consequently led to the overloading of transformers, transmission, and distribution lines. Despite the overwhelming advantages of renewable energy sources, there are few major issues associated with them. For example, the injection and detachment of DGs into the current power system causes disparity among produced power along with connected load, thus distracting system’s equilibrium and causes unwanted voltage and frequency oscillations and overshoots. These oscillations and overshoots may cause the failure of connected equipment or power system if not properly controlled. The investigation as such challenges to improve the frequency and voltage, the islanded’s power regulation and connected MG under source and load changes, which contain classic and artificial intelligence techniques. Moreover, these techniques are used also for economic analysis. To evaluate the exhibitions of microgrid (MG) operations and sizing economic analysis acts as a significant tool. Optimization method is obligatory for sizing and operating an MG as reasonably as feasible. Diverse optimization advances remain pertained to microgrid to get optimal power flow and management.